«Червона книга України. Рослинний світ». Післямова - Дідух, Я.П. (Український ботанічний журнал, 2010)
Дан анализ третьего издания «Красной книги Украины» (2009), в которую включено 826 видов (611 — сосудистых растений, 46 — мохообразных, 60 — водорослей, 52 — лишайников, 57 — грибов). Освещены принципы подбора видов, приводится сравнительная оценка категорий, принятых в Украине и МСОП, их количественное распределение по геоботаническим и административным регионам. Публикуются полный список видов сосудистых растений и их категоризация. Results of publication of the third edition of the Red Data Book of Ukraine (2009) are generalized. This edition includes 826 species (611 vascular plants, 46 bryophytes, 60 algae, 52 lichens, and 57 fun gi). Approaches to species selection are discussed; a comparative assessment of conservation categories accepted in Ukraine and by IUCN is provided, as well as species distribution according to phytoceonological and political regions. The complete list of vascular plants and their categories is provided.